P‐7.3: Study on Transmittance, Color Shift and Gamut of Dielectric Multi‐layers. (4th October 2019) - Yi, Ning-Bo; Li, Li-Xia; Long, Si-Bang; Yan, Sen; Zhao, Feng; Chiu, Chung-Yi; Ray, Lin; Ge, Shi-Min; Li, Shan; Zhang, Sheng-Dong
Abstract : The layered structure of SiOx and SiNx is a good candidate to be gate insulator and passivation layers in IGZO TFT. However, this complex layered structure could introduce issues of transmittance, color shift and gamut change at aperture area in single glass of TFT side.